2011
DOI: 10.5402/2011/315432
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Needle Stick Injuries in Healthcare Occupations: An Integrative Review of the Literature

Abstract: Needlestick injuries frequently occur among healthcare workers, introducing high risk of bloodborne pathogen infection for surgeons, assistants, and nurses. This systematic review aims to explore the impact of both educational training and safeguard interventions to reduce needlestick injuries. Several databases were searched including MEDLINE, PsycINFO, SCOPUS, CINAHL and Sciencedirect. Studies were selected if the intervention contained a study group and a control group and were published between 2000 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…Regarding the gender of patients who suffered accidents, most were female. Other studies have found similar percentages (15)(16) . In the Brazilian state of São Paulo, between 2007 and 2010, 33,856 accidents were reported, of which 25,788 (76.2%) involved women (12) .…”
Section: Discussionsupporting
confidence: 70%
“…Regarding the gender of patients who suffered accidents, most were female. Other studies have found similar percentages (15)(16) . In the Brazilian state of São Paulo, between 2007 and 2010, 33,856 accidents were reported, of which 25,788 (76.2%) involved women (12) .…”
Section: Discussionsupporting
confidence: 70%
“…The prevalence of needle stick injury in our study is the highest among the medical students (42.1%), followed by medical officers (26.3%), staff nurses (15.8%), house officers (10.5%), specialist (5.3%) and no cases was reported among the nursing students (Graph 1). A Siberian study reported the prevalence of needle stick injury among medical student as 9.8% [11] and in the study conducted by Fernanda and Larissa et al in Brazil it was reported to be 20.9% [12] A recent study showed prevalence of needle stick injury is 19.9% in medical students and majority of it occurred at medical ward . [13] Lack of experience, increased workload and tiredness were the main reasons for the occurrences of needle stick injuries which are similarly observed in other studies involving medical students where it was noted that it is likely due to an increase in the number of procedures to be performed by the students as they progress through their semesters, inexperience in performing the medical procedures, increased workload and fatigue thus leading to needle stick injuries [14] .…”
Section: Discussionmentioning
confidence: 99%
“…[14] The majority of the study group in our study were under 25 years of age (63.9%)) and based on our results, the older age group is 2.7 times (1/0.37) more likely to get needle stick injury because of they have a longer career span as compared to those of a younger age group. However, it is found that the risk is expected to be higher in relatively younger age group as they are least experienced and they tend to ignore the universal work precaution [12] .…”
Section: Graph 1 Relationship Between Medical Profession and Prevalementioning
confidence: 99%
“…Needle stick injury is a common and serious event defined as the accidental puncturing the superficial tissue may leading the unintended contact with blood or body fluids during an intervention (Sharma, Rasania, Verma & Singh, 2010;Yang & Mullan , 2011). The common form of the needle stick among health care workers can be occurred while recapping of needle that may result in the needle stick injury and thus transferring infectious strains via injured skin to blood stream (Galougahi, 2010;Colombo, Masserey & Ruef, 2011).…”
Section: Introductionmentioning
confidence: 99%